2003
DOI: 10.2337/diacare.26.5.1338
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Undiagnosed Diabetes and Other Hyperglycemia States

Abstract: OBJECTIVE -To evaluate screening strategies based on fasting plasma glucose (FPG), clinical information, and the oral glucose tolerance test (OGTT) for detection of diabetes or other hyperglycemic states-impaired fasting glucose (IFG) and impaired glucose tolerancemeriting clinical intervention. RESEARCH DESIGN AND METHODS -We studied 8,286African-American and white men and women without known diabetes, aged 53-75 years, who received an OGTT during the fourth exam of the Atherosclerosis Risk in Communities Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Whether our results generalize to other populations is an important area for future research. The Atherosclerosis Risk in Communities Study (18) concluded that twothirds of those classified at the lower (100 -109 mg/dl) IFG cut point had either diabetes or IGT. Thus, because many patients with IFG also have IGT, interventions proven effective in IGT populations (19 -22) would likely also apply to the majority of patients with IFG.…”
Section: Figure 1-progression From Normal Fasting Plasma Glucose To Smentioning
confidence: 99%
“…Whether our results generalize to other populations is an important area for future research. The Atherosclerosis Risk in Communities Study (18) concluded that twothirds of those classified at the lower (100 -109 mg/dl) IFG cut point had either diabetes or IGT. Thus, because many patients with IFG also have IGT, interventions proven effective in IGT populations (19 -22) would likely also apply to the majority of patients with IFG.…”
Section: Figure 1-progression From Normal Fasting Plasma Glucose To Smentioning
confidence: 99%
“…The use of the DRS as an initial screening instrument, followed by the measurement of FBG in individuals with a score Ն9 and by the OGTT in individuals with an FBG between 5.6 and 6.9 mmol/l, would lead to the identification of 83% of the cases of unknown diabetes and 57% of IGT cases, at a cost of an OGTT in 38% of the sample and an FBG in 64%. Therefore, the yield of this strategy would be almost identical to that obtained in the ARIC study (21), but with a much simpler and less expensive approach, considering that only two-thirds of the patients needed the FBG measurement with our strategy. It is important to note that the same detection rate would be obtained with a strategy using an FBG measurement as the initial step, followed by an OGTT in individuals with an FBG of 6.1-6.9 mmol/l.…”
Section: Igloo Study Groupmentioning
confidence: 80%
“…The yield of the different screening strategies is summarized in Table 3, where we report the results obtained in the IGLOO population as well as those deriving from the simulations based on different scenarios, with a prevalence of glucose abnormalities ranging between 5 and 20%. From the table it emerges that the best compromise between number of cases detected and cost per case detected is represented by the screening strategy using the DRS as initial instrument, with an FBG performed in individuals with a (15)(16)(17)(18)(19)(20), only a few studies have addressed the problem of also identifying those with asymptomatic hyperglycemia requiring clinical intervention (21,22). In particular, in the Atherosclerosis Risk in Communities (ARIC) study, a clinical detection rule was developed that, associated with FPG and/or OGTT, led to the detection of 86.3% of the cases of diabetes and 52.4% of the cases of IGT, with 39.6% of the patients needing an OGTT (assuming that patients with IFG needed to be reclassified) (21).…”
Section: Igloo Study Groupmentioning
confidence: 99%
“…Use of glucose levels for screening has revealed that post-challenge glucose is a more uniform predictor of progression from IGT to diabetes as compared with fasting glucose [29]. Moreover, fasting glucose measurements often fail to recognise both IGT and diabetes [30,31], and poor sensitivity is obtained even with lower cut-off levels [32,33]. Previous studies of RPG and RCG have frequently not included AROC values [34,35], but RCG can be efficient when combined in an equation with postprandial time, age, sex and BMI [36].…”
Section: Discussionmentioning
confidence: 99%